ZAKAT AND EMPOWERMENT MICRO, SMALL AND MEDIUM BUSINESS (CASE ON NATIONAL AMIL ZAKAT AGENCY IN PALOPO) - Bakri, Adzan Noor; Daud, Akhmad Syarifuddin (Jurnal Syarikah : Jurnal Ekonomi Islam, 2019)
This paper aims to analyze the role of zakat in the empowerment of Micro, Small and Medium Business ((UMKM)) in Palopo, and  secoundly to analyze the management of utilization of zakat by BAZNAS Palopo City in the empowerment of UMKM, and  thirdly to formulate zakat potential and productivity by BAZNAS Palopo City as venture capital investments of UMKM. This study used a qualitative approach. Primary data taken from research informant. The result of the research showing  that the role of ZIS funds collected by BAZNAS Palopo city in empowering UMKM in Palopo is fundamental. This is demonstrated by the many businesses types of UMKM obtaining qardul hasan financing from BAZNAS Palopo city.  utilization management of ZIS fund conducted by BAZNAS of Palopo city in recent years aimed at financing on productive and the potential sectors to be developed.  The huge potential of ZIS funds owned by Palopo city based on the calculations in this study is Rp.8.539.124.00. With the huge potential amount, it can help the business capital as many as 570 units, 170 units of small businesses, and 85 units for medium-sized business.